Optimization Interpersonal Communication in Education and Learning contest at MTs.N Parepare City - Ahdar; Rahman; Musyarif (Universitas Muhammadiyah Palu, 2024)
This research examines How interaction learning This research examines How interaction learning in this research examines How interaction learning at MTs.N Parepare Parepare City, and how application interpersonal communication in the education and learning process at MTs.N Parepare Parepare City. This research was conducted at MTs.N Parepare Parepare City, using a qualitative research survey approach, the population is participant educate class VII as many as 62 people and the sample as many as 31 people, as well educator MTs.N Parepare Parepare City, with data collection techniques used, namely: observation, interviews, questionnaires, and documentation, as well as data analysis qualitative. In this study it was found , several matter including : first, interaction learning at MTs.N Parepare Parepare City walk conducive and effective, though Still There is constraint limitations facilities and funds. Second In principle, educators apply interpersonal communication in the education and learning process at MTs.N Parepare Parepare City, though Still need improved. Aspect existing interpersonal communication maximum is emphasis importance material lesson learned (51.6%), explanation material in a way communicative and logical (48.8%), bringing it closer distance with participant educate in teaching (61.3%), using internal body movements teach or kinesics (74.2%), using expression face in teaching (51.6%), effort explain with understood language participant educate (58.1), effort serve with clear mention of words and sentences (67.7%), effort embed love of material lesson (77.4%), and presentation effective Because similarity background behind culture and religion (90.3%). Meanwhile, what is necessary improved is design pattern presentation material (9.7%), visualization material lessons (9.7%), encouraging act positive in accordance material (35.5%), using deep verbal description teaching (3.2%), using paralinguistics (25.8%), using instruction appearance (22.6%), and effort equalize perception (25.8%). Polman district, and how application interpersonal communication in the education and learning process at MTs.N Parepare Parepare City. In this study it was found, several matter including : first, interaction learning at MTs.N Parepare Parepare City walk conducive and effective, though Still There is constraint limitations facilities and funds. Second In principle, educators apply interpersonal communication in the education and learning process at MTs.N Parepare Parepare City, though Still need improved . Aspect existing interpersonal communication maximum is emphasis importance material lesson learned (51.6%), explanation material in a way communicative and logical (48.8%), bringing it closer distance with participant educate in teaching (61.3%), using internal body movements teach or kinesics (74.2%), using expression face in teaching (51.6%), effort explain with understood language participant educate (58.1), effort serve with clear mention of words and sentences (67.7%), effort embed love of material lesson (77.4%), and presentation effective Because similarity background behind culture and religion (90.3%). Meanwhile, what is necessary improved is design pattern presentation material (9.7%), visualization material lessons (9.7%), encouraging act positive in accordance material (35.5%), using deep verbal description teaching (3.2%), using paralinguistics (25.8%), using instruction appearance (22.6%), and effort equalize perception (25.8%).